Patient and clinician experiences with an emergency department‐based mental health liaison nurse service in a metropolitan setting. (13th August 2020) - Wand, Timothy; Collett, Gemma; Cutten, Alexa; Buchanan‐Hagen, Sally; Stack, Amanda; White, Kathryn
Abstract: As part of a larger multi‐site translational research project this study explored patient and staff experiences, perspectives, and recommendations in relation to a mental health liaison nursing (MHLN) team established in the emergency department (ED) of a metropolitan hospital in New South Wales, Australia. Semi‐structured interviews were conducted with a sample of ED patients ( n = 26), ED nurses ( n = 10), ED consultants ( n = 9), and members of the consultation–liaison psychiatry team ( n = 5). Data were analysed thematically. Patients emphasized the numerous therapeutic qualities of the MHLN role, the promptness with which they were seen and the value of follow‐up. Privacy was identified as important, and some negative experiences were reported. Staff identified that the MHLN team are able to respond to a variety of ED presentations in a timely manner. There was recognition that the MHLN team needs to be integrated within the ED as a specialist resource that builds ED capacity. Consistent staffing of the MHLN team with designated clinicians was also considered essential. Integrating a nurse practitioner‐led MHLN team within the ED has demonstrated multiple benefits for patients, ED staff, and overall service provision. Incorporating a specialist mental health nursing service within the ED builds confidence in ED clinicians. Members of the psychiatry team also acknowledge the value of aligning the clinical governance of the MHLN team within the ED and the reduced workload this model of care has on their service provision to ED, freeing them up to concentrate on their broader general hospital role.